Physical Properties Of Particle-Reinforced Particle Board And Gaba Fiber Using Pvac (Polyvinyl Acetate) Filler - Sudarman Samad; Ardi Basri; Utdin Furqon Amali; Muhammad Rahmat (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Traditional materials are often selected and used in the construction of houses and buildings based on local knowledge that has been tested for centuries. The use of sago leaf stalks as a building material has several advantages. They are generally easy to find in tropical areas and have natural properties that allow good air circulation, thereby helping to keep the indoor temperature cool. In addition, this material is also environmentally friendly because it can decompose properly and can be renewed naturally. In an effort to preserve these cultural and traditional values, we can take several steps. First, public education and awareness about the advantages of traditional building materials need to be improved. Organizing workshops or seminars to share knowledge about the use of traditional materials and their benefits can help increase people’s appreciation of these materials. The use of sago stalks as building materials can be part of cultural conservation and environmental preservation efforts. By combining traditional knowledge with modern innovation, we can create building solutions that are environmentally friendly, sustainable and maintain our cultural heritage. By using PVAc filler, this study aims to study its effect on the physical properties of the resulting composite material. Variations in the composition of the mix will enable the identification of changes in the characteristics of the composite board and efforts to obtain optimal physical properties.